Streptomyces catenulae as a Novel Marine Actinobacterium Mediated Silver Nanoparticles: Characterization, Biological Activities, and Proposed Mechanism of Antibacterial Action - Khalil, Maha A.; El-Shanshoury, Abd El-Raheem R.; Alghamdi, Maha A.; Sun, Jianzhong; Ali, Sameh S. (Frontiers in Microbiology, 2022)
Biosynthesized silver nanoparticles (Bio-SNPs) were synthesized from the marine actinobacterium strain Streptomyces catenulae M2 and characterized using a variety of techniques, including UV–vis spectrum, Fourier transform infrared spectroscopy (FTIR), energy dispersive x-ray (EDX), transmission electron microscopy (TEM), dynamic light scattering (DLS), surface-enhanced raman spectroscopy (SERS) and zeta potential. The antibacterial activity of Bio-SNPs alone and in combination with antibiotic was evaluated using a microtiter-dilution resazurin assay against multidrug resistant (MDR) bacteria. Bio-SNPs' minimum inhibitory concentration (MIC) against bacterial strains was determined. To assess the synergistic effect of Bio-SNPs in combination with antibiotics, the Fractional Inhibitory Concentration Index (FICI) was calculated. While the safety of Bio-SNPs in biomedical applications is dependent on their use, the in vitro cytotoxicity of Bio-SNPs on normal human epithelial colon cells (NCM460) and human colorectal adenocarcinoma cells (CaCo2) was evaluated using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay and cell lactate dehydrogenase (LDH) release. The presence of bio-SNPs was revealed by UV–vis spectroscopy, which revealed a peak in the Surface Plasmon Resonance (SPR) spectrum at 439.5 nm. Bio-SNPs were spherical in shape and small in size (average 33 nm by TEM, 58.8 nm by DLS), with good stability (-30 mV) and the presence of capping agents. Bio-SNPs had MIC values ranging from 2 to 64 g/ml against the bacteria tested. The MIC for P. aeruginosa was the lowest (2 μg/ml). Antibiotics have been shown to have a significant synergistic effect when combined with SNPs against tested bacteria. SNPs exhibited dose-dependent cytotoxicity against NCM460 and CaCo2 cancer cells, with the latter exhibiting far greater toxicity than the former. Cell viability decreased from 99.3 to 95.7 % and from 92.3 to 61.8 %, respectively, while LDH leakage increased from 200 to 215 nmol/ml and from 261 to 730 nmol/ml. For the MTT and LDH assays, the half inhibitory concentrations (IC50) were 79.46 and 10.41 µg/ml, respectively, and 89.4 and 19.3 µg/ml, respectively. Bio-SNPs were found to be biocompatible and to have anti-inflammatory activity. Bio-SNPs are highly appealing for future nanomedicine applications due to their antibacterial and biocompatible properties, as well as their inherent "green" and simple manufacturing.